PERUBAHAN POLA KONSUMSI RUMAH TANGGA SAAT COVID-19 (Studi Kasus di Kelurahan Drajat, Kota Cirebon, Jawa Barat) - Afriliyendra Putri Bestari; Trisna Insan Noor (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Covid-19 is a global pandemic that impacts all sectors. Household is one of the sectors that impacted, and the conditions during the Covid-19 pandemic have been changing especially a decrease in the household consumption expenditure. The purpose of this research is to understand the household food consumption pattern and its relation with the characteristics of respondents. This research used a quantitative descriptive design with a survey method that located in RW 02 Drajat Sub-district, Cirebon City, on October-November 2020. The numbers of research samples are 61 respondents consisting of housewives. The analysis method used is crosstabs method. The results showed that the average age of the respondents was 15-64 years old, the number of family members is 3 persons, the household income per month before and during Covid-19 are IDR 2,000,000-IDR 3,000,000 and < IDR 1,000,000, the education achieved is senior high school or vocational high school, the job is as a housewife, and 62,30% jobs affected due to Covid-19. The household consumption patterns have been changing specifically a decrease in household food consumption expenditure on almost all food commodities except for consumption of vegetable commodities due to the rising prices. However, the amount of food and other non-food consumption tends to remain and decrease. The results showed that the household income and husband’s job have a relation with the household consumption patterns changing, it is indicated by the value of Asymp. Sig. (2-sided) < 0.05, while other variables have no relation with the household consumption patterns changing.